Philosophical Reflection on Selected Contemporary Rituals of the Everyday - Jakubovská, Viera; Jakubovská, Kristína; Moravčíková, Erika (Journal of Education Culture and Society, 2025)
Thesis. The present study explores the issue of ritualised behaviour in the context of traditional and non-traditional, individual and collective forms of social life. The research questions map the significance and functions of rituals in contemporary society, as well as the reasons behind individual and collective return to them. Methods. The authors define and redefine basic terms and traditional characteristics of ritual and elaborate on their current specifics. They use a heuristic method of research and work with case studies, interpreting and reinterpreting relevant domestic and foreign sources. Results. In comparing traditional and contemporary definitions and characteristics of rituals, we note that 1/ ritual continues to have a place as part of sociocultural regulators in current times, 2/ the dynamism and instability of postmodern society is reflected in the transformations and diversity of modern rituals, 3/ contemporary rituals are less formally binding and have a less fixed form, are more individualised, and are manifested in different spheres of human life (both formal and informal, including in everyday life). Conclusion. Regardless of whether contemporary rituals are collective or individual, whether they are religious or profane, we cannot deny their importance in the intellectual and social development of contemporary human person and the formation of community. Some features of ritual remain, others are modified and new ones are added as rituals are located in areas where they were not originally found. Even today, rituals fulfil various functions in the lives of individuals and groups.